Hermeneutika Penyusunan Materi Komsel Gereja Beraliran Pentakostal - Twin Hosea Widodo Kristyanto; Edward Everson Hanock; Andreas Eko Nugroho; Twin Yoshua R. Destyanto (Sekolah Tinggi Teologi Intheos Surakarta, 2022)
Abstract. This study aims to explain the hermeneutic procedure for the preparation of the COOL Youth Supplement and to analyze its suitability with the Pentecostal hermeneutic concept. COOL Youth Supplement is a term for youth cell group material at GBI Gatot Subroto (GBI Gatsu) Jakarta, a church of the Classical Pentecostal. This research was carried out using qualitative methods through a literature study and phenomenology approach. The results showed that the preparation of the GBI Gatsu COOL Youth Supplement was in accordance with the concept of Pentecostal hermeneutics. Except, in the aspect of the study of the genre of the book and the faith professing of the Holy Spirit in the Pentecostal community which has not been applied in the preparation of the GBI Gatsu COOL Youth Supplement.Abstrak. Penelitian ini bertujuan untuk menjelaskan prosedur hermeneutika penyusunan Suplemen COOL Youth dan menganalisis kesesuaiannya dengan konsep hermeneutika Pentakostal. Suplemen COOL Youth adalah istilah untuk materi komsel pemuda di GBI Gatot Subroto (GBI Gatsu) Jakarta, sebuah gereja dengan aliran Pentakostal Klasik. Penelitian ini dilaksanakan dengan menggunakan metode kualitatif melalui pendekatan studi literatur dan fenomenologi. Hasil penelitian menunjukkan bahwa bahwa penyusunan Suplemen COOL Youth GBI Gatsu sesuai dengan konsep hermeneutika Pentakostal. Kecuali, pada aspek studi genre kitab dan kesaksian Roh Kudus dalam komunitas Pentakostal yang belum diterapkan dalam penyusunan Suplemen COOL Youth GBI Gatsu.